How much privacy we still have on social network? - Chewae, Mafaisu; Hayikader, Sameer; Hasan, Muhamad Hairulnizam; Ibrahim, Jamaludin (IJSRP.ORG, 2015)
Recently, internet is one of the most efficient and effective ways to communicate and sharing the information especially in terms of social networking sites. With over billions of users connected through online social network and due to the popularity of social network sites, more people are concerning about the privacy and it has become an important issue. In this paper we will review how the current privacy plays on social network sites, analyze how personal information is being influenced by internet and social network, and also we will discuss how the privacy become a risk and how to employ security awareness to avoid privacy risk.